Leadership Styles and Burnout: is there an association? - Constanti, Panayiotis; Zopiatis, Anastasios (My University, 2010)
The primary purpose of the study was to investigate the association between leadership styles and burnout among hospitality managers currently working in the industry of Cyprus. Specifically, transformational, transactional and passive/avoidance were investigated in order to establish which leadership style is more prone to burnout effects. Design/methodology/approach - Adopting a quantitative approach, the Multifactor Leadership Questionnaire (MLQ 5X-Short) was utilized to allow research participants to describe their leadership style as they perceive it. In addition, the most widely acknowledged tool for measuring burnout, the Maslach Burnout Inventory (MBI), was also incorporated in the questionnaire, which was then distributed to 500 hospitality managers in Cyprus. A number of hypotheses, reflecting the primary objective of the study, were postulated. Findings - The findings suggest that transformational leadership has a significant positive association with personal accomplishment and is negatively related to emotional exhaustion and depersonalization. In addition a positive relationship exists between passive avoidance leadership and emotional exhaustion and depersonalization. Finally, individuals with a passive avoidance leadership style exhibited higher levels of burnout. Research limitations/implications - It is well documented in the literature that surveys measuring sensitive issues, such as leadership styles and burnout levels, have inbuilt limitations (Hunt, 1999; Antonakis et al., 2003). With regards to leadership, the authors acknowledge that they were not able to replicate the original nine-factor solution of the MLQ 5X, therefore, findings should be viewed with caution. The second limitation is the small sample size (n=131) and the homogeneity of the sample, which limit the generalizability of the findings. Practical implications - The findings have a practical relevance to both hospitality stakeholders and academic scholars who wish to further explore the leadership-burnout association. In addition, Human Resources practitioners could utilize the findings when developing strategies for recruiting and developing leaders. Originality/value - The paper adds to existing knowledge by investigating an issue presented in just a few hospitality-related studies. While burnout and leadership separately, have captured the attention of hospitality researchers, studies investigating their association are ubiquitous by their absence. The insights derived from this paper are of value to academic scholars wishing to build on this exploratory investigation.
Keywords: Leadership styles; Burnout; Hospitality Industry; Cyprus